Deprivation of Liberty: Has the European Court of Human Rights Recognised a ‘Public Safety’ Exception? - Donna Cline (Utrecht Journal of International and European Law, 2013)
The European Court of Human Rights held in Austin Others v The United Kingdom that the police confinement of a crowd of protestors for up to seven hours, or 'kettling', did not constitute a deprivation of liberty in violation of Article 5 of the European Convention of Human Rights. Austin was the first time the Court considered the application of Article 5 to the practice of kettling. The Court's previous Article 5 jurisprudence demonstrates that when analysing whether an individual has been unlawfully deprived of his or her liberty, the Court will consider the type of measure, its duration, its effects on the individual, and the manner of implementation of the restrictive measure. In Austin, the Court introduced a new factor in this analysis - the context in which the measure is imposed. This article examines the Court's deprivation of liberty jurisprudence, as well as the Article 5 exceptions to the prohibition of deprivation of liberty. Finally, the Court's finding in Austin is analysed to determine whether it now recognises a 'public safety exception' to Article 5.